Inventarisasi Mamalia di Kawasan Suaka Margasatwa Gunung Raya Kabupaten Ogan Komering Ulu Selatan Provinsi Sumatera Selatan - Rizky Hidayat; Indra Yustian; Doni Setiawan (Jurnal Penelitian Sains, 2018)
Mammals is one of the framers class of the diversity of wildlife on an ecosystem. The data about mammal’s diversity in Gunung Raya Wildlife Reserveare still limited for the biodiversity management especially on mammals in this area. One methods to know the presence of mammals in Gunung Raya Wildlife Reserve is by doing the inventory. The aim of this research is to know the presence of mammals and its conservation status in Gunung Raya Wildlife Re-serve South Ogan Komering Ulu Regency South Sumatera Province. This research was done from March 2017 to April 2018 in Gunung Raya Wildlife Reserve, exactly on Pasir Bintang, Mesagi, Bukit Lebong, and Manduriang South Ogan Komering Ulu Regency South Sumatera Province. The method used for this research was by Reconnaissance Walk. The data collected by direct observation, camera trap, life trap, mist net, activity track and interviews. There are 23 species of mammals recorded in Gunung Raya Wildlife Reserve by this research, 9 of those species listed as protected animals based on PerMen LHK No. 20 Thn 2018, which are Symphalangus syndactylus, Nesolagus netscheri, Manis javanica, Lariscus insignis, Ratufa affinis, Tapirus indicus,Presbytis melalophos, Trachypithecus cristatusand Helarctos malaya-nus and based on IUCN 2018 there are 1 species which is Manis javanica categorized as CR (Critically Endangered) which in the near future will be threatened of the extinction.